Cryopreservation Effect on Immunologic Activity and Phenotypic Composition of Human Embryonic Liver Lymphoid Cells - Petrenko, Yu. A.; Tarasov, A. I.; Grischenko, V. I.; Petrenko, A. Yu. (Problems of Cryobiology and Cryomedicine, 2002)
Authors studied the phenotype of freshly isolated and cryopreserved cells from human embryonic liver (HEL), and its capability to provoke an immune response of adult donor lymphocytes (ADL) during co-culturing. Flow cytometry data did not allow to reveal the statistically significant expression of lymphoid commitance markers (CD1+, CD10+, CD5+, CD20+) and showed the insignificant content of CD7+Â and CD13+Â cells in embryonic liver (less than 1%). In freshly isolated and cryopreserved suspensions the CD45+Â and HLA-DR+Â cells are presented in the greatest extent (2.65Â±0.32% and 7.51Â±1.35%, correspondingly). Low content of lymphoid cells was accompanied by poor immunogenic activity of liver cells, studied in mixed lymphocyte culture (MLC). Cryopreservation allows to keep the proliferative activity of HEL cells, and does not influence its phenotype and immunological activity.